Association Between Oral Microbiota and Human Brain Glioma Grade: A Case-Control Study - Wen, Yuqi; Feng, Le; Wang, Haorun; Zhou, Hu; Li, Qianqian; Zhang, Wenyan; Wang, Ming; Li, Yeming; Luan, Xingzhao; Jiang, Zengliang; Chen, Ligang; Zhou, Jie (Frontiers in Microbiology, 2021)
Gliomas are the most prevalent form of primary malignant brain tumor, which currently have no effective treatments. Evidence from human studies has indicated that oral microbiota is closely related to cancers; however, whether oral microbiota plays a role in glioma malignancy remains unclear. The present study aimed to investigate the association between oral microbiota and grade of glioma and examine the relationship between malignancy-related oral microbial features and the isocitrate dehydrogenase 1 (IDH1) mutation in glioma. High-grade glioma (HGG; n = 23) patients, low-grade glioma (LGG; n = 12) patients, and healthy control (HCs; n = 24) participants were recruited for this case-control study. Saliva samples were collected and analyzed for 16S ribosomal RNA (rRNA) sequencing. We found that the shift in oral microbiota β-diversity was associated with high-grade glioma (p = 0.01). The phylum Patescibacteria was inversely associated with glioma grade (LGG and HC: p = 0.035; HGG and HC: p < 0.01). The genera Capnocytophaga (LGG and HC: p = 0.043; HGG and HC: p < 0.01) and Leptotrichia (LGG and HC: p = 0.044; HGG and HC: p < 0.01) were inversely associated with glioma grades. The genera Bergeyella and Capnocytophaga were significantly more positively correlated with the IDH1 mutation in gliomas when compared with the IDH1-wild-type group. We further identified five oral microbial features (Capnocytophaga Porphyromonas, Haemophilus, Leptotrichia, and TM7x) that accurately discriminated HGG from LGG (area under the curve [AUC]: 0.63, 95% confidence interval [CI]: 0.44–0.83) and HCs (AUC: 0.79, 95% CI: 0.68–0.92). The functional prediction analysis of oral bacterial communities showed that genes involved in cell adhesion molecules (p < 0.001), extracellular matrix molecule–receptor interaction (p < 0.001), focal adhesion (p < 0.001), and regulation of actin cytoskeleton (p < 0.001) were associated with glioma grades, and some microbial gene functions involving lipid metabolism and the adenosine 5’-monophosphate-activated protein kinase signaling pathway were significantly more enriched in IDH1 mutant gliomas than compared with the IDH1-wild-type gliomas. In conclusion, our work revealed oral microbiota features and gene functions that were associated with glioma malignancy and the IDH1 mutation in glioma.